2010
DOI: 10.1002/dvdy.22387
|View full text |Cite
|
Sign up to set email alerts
|

Subdivisions of chick diencephalic roof plate: Implication in the formation of the posterior commissure

Abstract: The subcommissural organ (SCO) is a roof plate differentiation located in the caudal diencephalon under the posterior commissure (PC). A role for SCO and its secretory product, SCO-spondin, in the formation of the PC has been proposed. Here, we provide immunohistochemical evidence to suggest that SCO is anatomically divided in a bilateral region positive for SCO-spondin that surrounds a negative medial region. Remarkably, axons contacting the lateral region are highly fasciculated, in sharp contrast with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…In the LDRP, these axons became fasciculated and advanced towards the MDRP, where some turned to the ipsilateral side (Stanic et al, 2010 and present work Figure 3 ). The trajectory of these axons can be divided into the following three stages ( Figure 6 ): (1) advance from the ventral region to the lateral RP; (2) fasciculation in the lateral RP; and (3) midline decision to turn towards the ipsilateral side or continue to the opposite side.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In the LDRP, these axons became fasciculated and advanced towards the MDRP, where some turned to the ipsilateral side (Stanic et al, 2010 and present work Figure 3 ). The trajectory of these axons can be divided into the following three stages ( Figure 6 ): (1) advance from the ventral region to the lateral RP; (2) fasciculation in the lateral RP; and (3) midline decision to turn towards the ipsilateral side or continue to the opposite side.…”
Section: Discussionmentioning
confidence: 51%
“…It was previously shown that SCO-spondin is secreted by the lateral diencephalic RP from the early stages of development, but expression was missing in the few midline RP cells (Stanic et al, 2010). In vivo and in vitro evidence shows that SCO-spondin is important for axon fasciculation, since axons located on the lateral RP are highly fasciculated in contrast to the defasciculated axons located on the midline, where some turn to the ipsilateral side (Stanic et al, 2010; discontinuous arrow in Figure 3B ). Immunohistochemical analysis of EphA7 expression at the HH30 stage revealed that this protein was expressed at the midline, specifically in cells lacking SCO-spondin (continuous arrows in Figures 3C,D ; double arrow in Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations